Experimental Study of the Pathogenicity of Pasteurella multocida Capsular Type B in Rabbits. Issue 2 (August 2015) - Katoch, S.; Verma, L.; Sharma, M.; Asrani, R.K.; Kumar, S.; Chahota, R.; Verma, S.
Summary: The increased frequency of isolation of Pasteurella multocida capsular type B from rabbitries in north-western India prompted this investigation into the role of this organism in inducing disease in rabbits. Ten rabbits were divided into two groups of five animals. Group I rabbits were infected intranasally (IN) with 1 ml of inoculum containing 2 × 10 5 colony forming units/ml, while rabbits in group II were given 1 ml phosphate buffered saline IN. The rabbits in group I developed respiratory distress, increased rectal temperature and severe dyspnoea, with death occurring 24–48 h post infection. The main pathological findings were severe congestion and haemorrhage in the trachea, fibrinopurulent pneumonia, bacteraemia and septicaemia. The nasal secretions of all group I animals contained P. multocida . These observations indicate that in addition to P. multocida capsular types A and D, P. multocida capsular type B can also be highly pathogenic for rabbits.